Análise de estruturas inspiradas em fractais aplicadas em antenas e superfícies seletivas de frequência - Batista, Yuri Max Vieira (2018)
The development of new fractal-based structures applied to planar technology has motivated many researchers around the world, who are very interested in the design of compact, stable, efficient, and low cost microwave devices and circuits for wideband and multiband frequency applications, with enhanced filtering (transmission or rejection), radiation or rejection characteristics, for example. Specifically, the geometry of traditional fractals have been widely used in the development of integrated circuits for microwaves and antennas because they have enhanced their frequency responses. However, in order to extract more advantages from the potential of these geometries, they must be changed according to particular applications. In addition, due to external interference, spatial filters, such as frequency selective surfaces (FSS), have become increasingly popular with the large growth in the use of wireless technologies, as they appear to be an excellent solution for predetermined frequency filtering. In addition, the use of traditional or new fractal geometries in these structures always brings particular contributions in improving their frequency responses. Therefore, the main objective of this work is to improve current FSS technology using known fractal geometries, which are modified, to take more advantage of the use of these geometries’ characteristics. Thus, using some different configurations of the same architecture, inspired by the Hilbert fractal, one can configure the structure of the FSS to obtain improved bandwidth, multi-band operations, good angular stability, and compactness, for example. In addition, these fractal-based structures exhibit characteristics to be investigated with respect to the size reduction of the patch element of the periodic array and to the modification of the antenna resonate frequencies. This work compiles the experiment of several fractal inspired antennas and FSS structures that resonate in different frequencies. Several prototypes are fabricated and measured to validate the simulation results. This work presents FSS geometries inspired on the Hilbert fractal, the infinite mirror fractal, and the Sierpinski triangle geometry, with additional modifications to ensure angular and multiband stability. In addition, the developed antennas are inspired on Sierpinski fractal geometries enabling multiband frequency behavior and gain increase.